How Consumers Perceive Towards Traditional or Modern Markets Proven by Consumer Preference Logistic Regression - Kyandra Riviera; Suharno; Pahrul Fauzi (Jurnal Ekonomi Pembangunan, 2022)
Indonesia is ranked 4th as the country with the most population in the world. The large population in Indonesia causes an increase in the demand for basic needs. A large population has caused the market that supplies basic needs to increase. Undeniably, some consumers have switched to the modern market because of the rapid development experienced by the current market. The current market can meet the needs of very diverse consumers. This study aims to determine whether the rapid growth of the modern market ensures that consumer preferences shift towards the current market. Analyze whether income factors, distance from home to the nearest traditional market and the closest modern market, facilities, and operating hours influence consumer preferences in choosing a place to shop for basic needs. This study uses logistic regression as a quantitative analysis. Based on the research and data analysis results, two variables affect consumer preferences: facilities and distance from home to the nearest modern market. In comparison, three variables do not affect consumer preferences: income, distance from home to the nearest traditional market, and operating hours. Based on the results obtained through interviews with as many as 110 respondents, there were 70 respondents, or 64 percent of respondents, chose to shop at the modern market. The thing that consumers want most when shopping is convenience. Consumers in Indonesia itself are very diverse. Therefore, traditional and contemporary markets can increase this convenience in several ways, such as the neat arrangement of goods, a clean environment, and big parking lots.